Australia's Middle Power Approach Towards Climate Change in Pacific Island - Narisya, Siti Dinda (Department of International Relations, Brawijaya University, 2021)
This article tends to examine the ways Australia approaching climate change in the region associated with its middle power status. Pacific Islands or Southwest Pacific Region is a regional territory that almost of all its surface covered by water. The region is prominent for having numbers of island countries or island states which are very dependent on natural conditions. They are vulnerable to the change of nature thus it hits their top national security. The issue of climate change in recent years has gotten more serious attention from all over the world and so does the pacific island region with no exception. Australia with its unique feature of being known as a middle power state and as the most secure nation in the region has served a distinctive approach on addressing the issue of climate change. The behavior and identity approach are adequately in line to establish certain strategies associated with middle power status in the role of guiding Australia’s foreign policy. Keywords: climate change, Island states, middle power, Australia, foreign policy.